Levosimendan versus dobutamine in septic cardiomyopathy: a randomized clinical trial on cardiac function and safety - Zhao, Feng; Wei, Haolei; Lin, Leqing; Wang, Hui; Zhang, Zhuxian; Guo, Liang (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aims to evaluate the clinical efficacy, safety, and impact on outcomes of levosimendan compared with dobutamine in patients with septic cardiomyopathy.MethodsA randomized clinical trial was conducted in patients with septic cardiomyopathy between December 2022 and March 2024. Eligible patients received either levosimendan or dobutamine in addition to standard sepsis treatments. Baseline characteristics, laboratory parameters, pulse index continuous cardiac output, clinical outcomes, and adverse reactions were recorded and compared between the two groups.ResultsA total of 50 patients were analyzed, with 25 patients in each group. The mean age was 76.4 (±12.3) years, and 28 patients (56%) were male. Baseline characteristics were comparable between groups. Following treatment, improvements were observed in both groups in left ventricular ejection fracture and levels of cardiac troponin I, B-type natriuretic peptide, cardiac index (CI), lactate, and norepinephrine infusion rate(all P < 0.05), with significantly greater improvements in the levosimendan group (P < 0.05). Additionally, the CI was higher in the levosimendan group compared to the dobutamine group (P < 0.05). No statistically significant differences were observed between groups in other pulse index continuous cardiac output variables, laboratory tests, clinical outcomes, or adverse reactions.ConclusionsIn patients with septic cardiomyopathy, levosimendan treatment resulted in greater improvements in cardiac function, hemodynamic stability, and tissue perfusion compared with dobutamine, without an increase in adverse reactions. Further studies are needed to evaluate the long-term effects of levosimendan on clinical outcomes in this patient population.Registration numberChiCTR2500101261.